Photosensitizing Effect of Hematoporphyrin IX on Immature Stages of Ceratitis capitata (Diptera: Tephritidae) - Pujol Lereis, Luciana Mercedes (2010)
Immature stages of Ceratitis capitata were tested as a model for hematoporphyrin IX (HP IX) phototoxicity. The lethal concentration 50 (LC(50)) of HP IX in the food was determined during postembryonic development until adult emergence as 0.173 mm (95% CI: 0.138-0.209). The corresponding HP IX LC(50) during the dispersal period alone was 0.536 mm (95% CI: 0.450-0.633). HP IX toxicity was compared against Phloxine B (PhB) (0.5 mm). HP IX elicited a mortality of 90.87%, which was mainly concentrated during prepupal and early pupal stages. PhB mortality was much lower (56.88%) and occurred mainly during the adult pharate stage. A direct correlation between light-dependent HP IX mortality, evidence of reactive oxygen species (ROS) and lipid peroxidation (conjugated dienes and thiobarbituric acid reactive substances) was established in C. capitata larvae. ROS were found to be very significant in both the brain and in the gut.